Package of practices for organic production of rapeseed-mustard - Choudhary, R L; Jat, R S; Singh, H V; Dotaniya, M L (Indian Farming, 2024)
In the last several years, agricultural research has primarily focused on immediate productivity gain and profit increase, relying mainly on external inputs, either neglecting or improper use of local resources. The long-term consequences of these faulty practices have emerged as deterioration in soil health and environmental quality, and ultimately the human health. Additionally, productivity and profitability from conventional agriculture production systems are either declining or remain stable. Therefore, alteration in crop production practices is need of the hour. Adoption of organic farming practices in rapeseed-mustard group of crops appears to be a good alternative option in the present context. In addition to protecting the soil and the environment, the organic farming may help to improve and sustain the productivity and quality of the produce. Thus, adoption of recommended production technologies of the organic management in rapeseed-mustard group of crops could be more remunerative for farmers and environment friendly as well.